Membangun Silaturahim di tengah Pluralistas Keagamaan di Indonesia: Sebuah Kajian Sosio-Teologis - Misray Tunliu (Sekolah Tinggi Teologi Baptis, Jakarta, 2022)
The most basic and most important component in the relation of religious pluralism is the creation of a sustainable relationship of friendship and dialogue, which is built by every believer by opening himself to pluralism without having to sacrifice substantive things in building the common good, in accordance with the values shared by the community. It is believed in the Holy Scriptures that each believer also believes in the national and state order which is regulated and bound by the UUD 1945, Pancasila, and within the framework of diversity, without sacrificing others in the name of any religion. Religion must be an answer that educates, inspires others to be closer to the Creator. Religion must be an agent of change that changes people who are not virtuous, have no morals into people who are virtuous and have a noble character in accordance with the nature of Allah, the ruler of life. AbstrakKomponen paling mendasar dan terpenting dalam relasi pluralisme keagamaan adalah terciptanya hubungan silaturahim dan dialog yang berkelanjutan, yang dibangun oleh setiap umat berkeyakinan dengan membuka diri terhadap pluralisme tanpa harus mengorbankan hal-hal yang sifatnya substantif dalam membangun kemaslahatan secara bersama, sesuai dengan nilai-nilai yang diyakini dalam Kitab Suci masing-masing umat berkeyakinan juga dalam tatanan berbangsa dan negara yang diatur dan diikat dalam UUD 1945, Pancasila dan dalam bingkai kebhinekaan, tanpa mengorbankan yang lain atas nama agama apapun. Agama harus menjadi jawaban yang mengedukasi, menginspirasi sesama untuk lebih dekat kepada Sang Khalik. Agama harus menjadi agen perubahan yang mengubah insan yang tidak berbudi pekerti, tidak berakhlak menjadi insan yang berbudi pekerti dan berakhlak mulia sesuai dengan natur Allah Sang penguasa kehidupan.